Suppressive effects on human flexion reflex induced by different pressure intensities and stimulation sites - OKADA, Kaoru; KAWAKITA, Kenji; ITOH, Kazunori; MURASE, Kentaro (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 1998)
Different intensities of pressure were applied to various tender or non-tender points and the suppressive effects on the flexion reflex were examined in 21 healthy humans (18-26 years), who gave informed consent. The sural nerve was stimulated transcutaneously with trains of 5 pulses at intervals of 13 sec (1.05-1.10x T, T : threshold) and evoked EMGs were recorded from the biceps femoralis muscle. Tender points in the contralateral forearm were detected by careful palpation, and conditioning pressure stimulation was applied at variousintensities by a push-pull gauge for 78 sec. Pressure applied to tender points induced slightly greater suppression of evoked EMGs than that to non-tender points (C statistics : time series analysis), although the difference was not significant (group comparison). Pressure intensities of ten and 50 % of pain tolerance pressure seemed to be adequate for suppression of EMGs in both tender and non-tender points. These results suggest that suppression of flexion reflex by pressure application in humans may be mediated by tactile and pain-related afferent fibers and the importance of adequate stimulus intensity for the induction of analgesic effects.